Role of mitochondria in inflammatory lung diseases - Venkata Ramireddy Narala; Sahithi Reddy Narala; Parasuraman Aiya Subramani; Kalpana Panati; Narasaiah Kolliputi (Frontiers Media S.A., 2024)
Mitochondria play a significant and varied role in inflammatory lung disorders. Mitochondria, known as the powerhouse of the cell because of their role in producing energy, are now recognized as crucial regulators of inflammation and immunological responses. Asthma, chronic obstructive pulmonary disease, and acute respiratory distress syndrome are characterized by complex interactions between immune cells, inflammatory substances, and tissue damage. Dysfunctional mitochondria can increase the generation of reactive oxygen species (ROS), triggering inflammatory pathways. Moreover, mitochondrial failure impacts cellular signaling, which in turn affects the expression of molecules that promote inflammation. In addition, mitochondria have a crucial role in controlling the behavior of immune cells, such as their activation and differentiation, which is essential in the development of inflammatory lung diseases. Their dynamic behavior, encompassing fusion, fission, and mitophagy, also impacts cellular responses to inflammation and oxidative stress. Gaining a comprehensive understanding of the intricate correlation between mitochondria and lung inflammation is essential in order to develop accurate treatment strategies. Targeting ROS generation, dynamics, and mitochondrial function may offer novel approaches to treating inflammatory lung diseases while minimizing tissue damage. Additional investigation into the precise contributions of mitochondria to lung inflammation will provide significant knowledge regarding disease mechanisms and potential therapeutic approaches. This review will focus on how mitochondria in the lung regulate these processes and their involvement in acute and chronic lung diseases.